LEARNING STYLE AND INTEGRATIVE THEMATIC LEARNING CONCEPT - Rina Oktafia Putri (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2017)
Learning is one of the main keys in achieving educational goals. Good learning is a learning that takes place effectively and efficiently. Integrative thematic learning should have the creativity and innovative that teachers do in order to produce creative learners. Each learner has different learning styles because of the background of environmental factors, thinking patterns and interactions. Activities and learning outcomes are influenced by internal factors, both physical and psychological, and external factors in the family, school, work or community environment. The principle of learning, affirming that learning: is a part of development, lasting a lifetime, influenced by innate factors, environment and maturity, covering all aspects of life, takes place at any place and time, with teachers or without teachers, varying from simple to complex